Determination of the values of certain motor and mental variables in the physical and sports education class of primary students - HARBOUCHE, MOHAMED; BENYOUCEF, DAHOU (sports creativity, 2024)
The study aims to assess some of the motor and mental variables of elementary students from the professors' point of view, and to learn the differences in the distraction, hypermobility, impulsivity, and gender. The sample of the study included 30 physical and sports education professors of the Sougueur city of Tiaret State, and we relied on the descriptive curriculum, using a questionnaire form. The final results resulted in a low level of these variables, statistically significant differences in distraction, impulsive hypermobility, in favour of males, and the study recommended dividing roles between parents and professors in the detection and treatment of such disorders. and sensitizing them to these disturbances that they overlook.